THE EFFECTIVENESS OF THINK PAIR SHARE OF COOPERATIVE LEARNING ON STUDENT'S MATHEMATICS LEARNING OUTCOMES OF THE VII GRADE - Adhitya Prasetyaningtyas; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The use of less effective learning models causes students less active when learning in the classroom so that student learning outcomes are low. This research aims to determine the effectiveness of cooperative learning model type think pair share towards the outcome of grade VII students' mathematic subject at State Junior High School (SMP Negeri) 2 Srandakan, Bantul 2nd semester of the academic year 2017/2018. This is quantitative research with the population of students grades VII in SMP Negeri 2 Srandakan, Bantul, of the academic year 2017/2018 consists of 6 classes. The sample was selected through random sampling. It was chosen that class VII B as an experiment class and class VII B as a controlling class. The method of data collection is by applying tests and documentation. The research instrument employed in this study is a multiple-choice question. The testing instruments used in this research are the validity test, differencing test, and reliability test. The data analysis methods used for the prerequisite test are normality testing, homogeneity test, and hypothetical test through t-test. According to the result of t-test from both sides, it was found out that =2,00932 and  = 2,00862 in which > . There was a difference in students' outcome using cooperative learning model of type think pair share, with the outcome of students learning by using direct learning model in class VII SMP Negeri 2 Srandakan, 2nd semester of the academic year 2017/2018. Also, based on the t-test of one side, it was found out that  = 2,00932 and  = 1,67592 in which  >  defined as the cooperative learning model of type think pair share is way more effective than direct learning model to the outcome of learning the mathematic subject of students in grade VII SMP Negeri 2 Srandakan, in the 2nd semester of the academic year 2017/2018.